2019
DOI: 10.24251/hicss.2019.019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Quantitative Measures on Understanding Inconsistencies in Business Rules

Abstract: Business Rules have matured to an important aspect in the development of organizations, encoding company knowledge as declarative constraints, aimed to ensure compliant business. The management of business rules is widely acknowledged as a challenging task. A problem here is a potential inconsistency of business rules, as business rules are often created collaboratively. To support companies in managing inconsistency, many works have suggested that a quantification of inconsistencies could provide valuable ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…As observed, business rules are utilized to govern the business process (Nagel et al, 2019). These business rules are widely used to control and influence the behaviour of a business in an information system context (De Jesus & De Melo, 2014;Ezekiel et al, 2018;Nagel et al, 2019). Generally, institutional policies and procedures function as business rules.…”
Section: Issues With Existing Quality Assurance Systems and Prevailin...mentioning
confidence: 99%
“…As observed, business rules are utilized to govern the business process (Nagel et al, 2019). These business rules are widely used to control and influence the behaviour of a business in an information system context (De Jesus & De Melo, 2014;Ezekiel et al, 2018;Nagel et al, 2019). Generally, institutional policies and procedures function as business rules.…”
Section: Issues With Existing Quality Assurance Systems and Prevailin...mentioning
confidence: 99%
“…Thus, culpability measures can pinpoint the actual causes of inconsistencies in WFMS cases as a driver for resolving modeling errors [6]. Nagel et al (2019) could show that such inconsistency metrics are associated with a better understanding of inconsistencies. In light of the unique big data challenges in WFMS, not only these (quantitative) insights themselves but also the speed of their use become important to foster the innovative and sustainable development of WFMS [19].…”
Section: Figure 1 Exemplary Business Process and Business Rulesmentioning
confidence: 99%
“…During the pretest, we found that one major problem was the lack of trust in the inconsistency metrics, as many participants preferred to double-check the implication of the quantitative insights manually. As a result of this, we refined the introductory slides in order to build more trust in the values, as our focus was an investigation of different visualization approaches, and the general advantage of the values themselves has already been evaluated in [15].…”
Section: Participantsmentioning
confidence: 99%
“…DMN has mainly been adopted in business process management (BPM) literature, which moves towards accommodating decision management into the paradigms of Separation of Concerns (SoC) and Service-Oriented Architecture (SOA), by externalising decisions and encapsulating them into separate decision models [2,[9][10][11][12][13]. Hence, the decisions are implemented as externalised services.…”
Section: Introductionmentioning
confidence: 99%